BOOK REVIEWS (Heythrop journal, 1995)
Books reviewed in this article: Cynics and Christian Origins. By F. Gerald Downing. A Study of Ignatius of Antioch in Syria and Asia (Studies in the Bible and Early Christianity 29). By Christine Trevett. The Emergence of Christian Theology. By Eric Osborn. Early Christian Poetry: A Collection of Essays Edited by J. den Boeft and A. Hilhorst. Sacred Biography: Saints and Their Biographers in the Middle Ages. By Thomas J. Heffernan. Angelic Monks and Earthly Men. By Ludo J. R. Milis. Evacute;γómμα: Studies in Honor of Robert Taft, S. J. Studia Anselmiana. Analecta liturgica, 17. Edited by E. Cam and others. The Byzantine and Early Islamic Near East I: Problems in the Literary Source Material. Edited by Averil Cameron and Lawrence I. Conrad. Christendom and Christianity in the Middle Ages: The Relations between Religion, Church and Society. By Adriaan H. Bredero. The Contest of Christian and Muslim Spain 1031–1157. By Bernard F. Reilly. Shield and Sword: Jewish Polemics against Christianity and the Christians in France and Spain from 1100–1500 (Texts and Studies in Medieval and Early Modern Judaism 8). By Hanne Trautner-Kromann. Living and Dying in England 1100–1540: The Monastic Experience. By Barbara Harvey. Scribes and Scholars at Salisbury Cathedral, c.1075-c.1125 (Oxford Historical Monographs). By Teresa Webber. Renaissance Philosophy (A History of Western Philosophy 3). By Brian P. Copenhaver and Charles B. Schmitt. Prophetic Rome in the High Renaissance Period. Essays edited by Marjorie Reeves. Beyond Charity. Reform Initiatives for the Poor. By Carter Lindberg. Marcello Cervini and Ecclesiastical Government in Tridentine Italy. By William V. Hudon. Interpretations of Erasmus c.1750-1920: Man On His Own. By Bruce Mansfield. F. D. Maurice and Unitarianism. By David Young. The Convert Cardinals: John Henry Newman and Henry Edward Manning. By David Newsome. Communication and Change in American Religious History. Edited by Leonard I. Sweet. New Dimensions in American Religious History: Essays in Honor of Martin E. Marty. Edited by Jay P. Dolan and James P. Wind. John Courtney Murray and the American Civil Conversation. Edited by Robert P. Hunt and Kenneth L. Grasso. American Catholics and the Formation of the United Nations (Melville Studies in Church History 4). By Joseph S. Rossi. Religion in Public Life. Edited by Dan Cohn-Sherbok and David McLellan. Dirty Hands: The Problem of Political Morality. By Steve Buckler. The Culture of Disbelief: How American Law and Politics Trivialize Religious Devotion. By Stephen L. Carter. The Church and Morality: An Ecumenical and Catholic Approach. By Charles E. Curran. Human Morality. By Samuel Scheffler. Religion and Mental Health. Edited by John F. Schumaker. Religion and Sexual Health. Edited by Ronald M. Green. Philosophy of Mind: An Introduction. By George Graham. Does God Exist? The Debate Between Theists and Atheists. By J. P. Moreland and Kai Nielsen, with contributions by Peter Kreeft, Antony Flew, William Lane Craig, Keith Parsons, Dallas Willard. Is God Real? Edited by Joseph Runzo. Passionate Reason: Making Sense of Kierkegaard's ‘Philosophical Fragments’. By C. Stephen Evans.